Development of communication tool for resident‐ and family‐led care discussions in long‐term care through patient and family engagement. (7th October 2021) - Cranley, Lisa; Sivakumaran, Gajan; Helfenbaum, Shoshana; Galessiere, Daniel; Meyer, Raquel; Duggleby, Wendy; McGillis Hall, Linda; McGilton, Katherine S.
Abstract: Background: Effective communication between residents (older adults), families, and the healthcare team supports person‐centred care. However, communication breakdowns can occur that can impact care and outcomes. The aim of this paper is to describe a feedback approach to developing a communication tool for residents and families to guide information sharing during care discussions with the healthcare team in long‐term care. Methods: Development of the communication tool included consultation with key stakeholders for their feedback and input. Following initial development of the tool template by our research team, we invited feedback from our study collaborators. Next, individual interviews and a focus group were conducted with family members, followed by individual interviews with selected residents from two long‐term care homes in Ontario, Canada. Participants were asked to provide input and feedback on the tool's content and usability and to share ideas for improving the tool. Content analysis was used to analyse the interview data. Results: Feedback from residents and family included suggestions to enhance the tool's content and use of plain language, and suggestions for potential application of the tool. Conclusion: Feedback highlighted the value of engaging residents and family members in the development of a communication tool. The communication tool offers a structured format to support participation of residents and families in information sharing for care discussions with the healthcare team.